WOMEN VOICES IN THE AUTOBIOGRAPHIES (International Journal of Food and Nutritional Sciences, 2023)
The present paper attempts to foreground the two women identities with reference to Bama’s Karukku and Madhavi Desai’s Kuniye Ghuma. Distinguished attitudes of the women are discussed in the shades of trials and challenges. Besides, it draws the attention towards the different regions, cultural backgrounds, traditions and established systems in the Indian Society. It also focuses on the lives of women within and outside the wedlock. Moreover, their visions are presented with realistic situations.